2007
DOI: 10.1007/s00436-006-0404-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of a cytosolic heat shock protein 70 from Naegleria fowleri

Abstract: A gene encoding a cytosolic heat shock protein 70 from pathogenic Naegleria fowleri (Nf-cHSP70) was identified. The Nf-cHSP70 was 2,062 bp in length with an open reading frame of 1,980 bp encoding 659 amino acid residues. The deduced amino acid sequence of the gene shared high sequence identities with HSP70s from other parasitic organisms and mammals. The characteristic domains, including N-terminal ATPase domain, calmodulin-binding domain, and EE(D)VD motif, found in HSP70s were also well conserved in this ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Previous studies reported that N. fowleri produced Nfa1 protein as the contact mechanism on the cell surface of Chinese Hamster Ovary target cells in coculture (Jeong et al 2005). In addition, cytosolic heat shock protein 70 was a new finding for heat tolerance and may relate to virulence of the amoebae (Song et al 2007). In this study, we propose the SK-N-MC cells as a gold standard model due to the high susceptibility to N. fowleri.…”
Section: Days Post-inoculation Total Viable Cells ( X 10 3)mentioning
confidence: 97%
“…Previous studies reported that N. fowleri produced Nfa1 protein as the contact mechanism on the cell surface of Chinese Hamster Ovary target cells in coculture (Jeong et al 2005). In addition, cytosolic heat shock protein 70 was a new finding for heat tolerance and may relate to virulence of the amoebae (Song et al 2007). In this study, we propose the SK-N-MC cells as a gold standard model due to the high susceptibility to N. fowleri.…”
Section: Days Post-inoculation Total Viable Cells ( X 10 3)mentioning
confidence: 97%
“…To investigate the role of HSPs in N. fowleri, Song et al (2007) cloned the gene encoding for cytosolic-HSP70 in N. fowleri and concluded that the definitive roles of the NfcHSP70 protein under induction condition are not clear, but it may protect the parasite from environmental temperature changes (Song et al 2007). Nevertheless, there are only very limited information available regarding its function in the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that Nf-cHSP70 gene encodes a protein with 660 amino acids residues, producing a molecular mass of 72 kDa. In addition, the recombinant Nf-cHSP70 protein showed strong antigenicity against mice sera, which were infected experimentally with N. fowleri (Song et al 2007) and showed 68% sequence identity to HSP70s in comparison with other organisms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations